Pintando janelas em muros: a arte como método vivencial de facilitação de grupos populares - Pinho, Ana Maria Melo de (2010)
The present research tried to investigate the meaning of art as a life experience method of facilitation of popular groups, contextualized in the field of an acting based on the communitarian psychology of freedom (GOIS, 2008). The field of investigation took place in an intervention in the Marrocos community, at the Grande Bom Jardim neighborhood, in the outskirts of Fortaleza, where a group of self esteem was implanted. The formation of this group arose from the need of actions in mental health in the shapes of communitarian psychology (GOIS, 2008), in a way to enter and take place under the psycho social and concrete conditions of oppression and suffering. The group used a dialogue and life experience facilitation methodology, integrating artistic activities, such as: music, dance, painting, collage, among others, as a way to deflagrate positive and integrating life experience, which could facilitate the process of human development and freedom. The art was here conceived as a symbolic system, capable of returning to the origin of conscience, the identity`s emotional and vital pre-reflexive dimensions. This methodology was also referred in the theoretical methodological model of Biodance. The specific goals of this investigation were to understand the meanings given by the participants to the artistic activities, relate these meanings built with the social cultural context, and also analyze the effect of the artistic activities in the ways of life of the group`s participants. The elected methodology was the ethnography and the phenomenology, considered as possibilities to enter the subjective experiences of the participants and their culture. The instruments of data collection were the participating observation and the qualitative collective interview. The analysis of data was made in a way to continually articulate the theory and reality lived, taking as reference the stages of treating and organization of the data postulated in the analysis of content (MYNAYO, 2008). I concluded that art, realized as a communitarian activity, inside a life experience and group context, can be revealed as a possibility of human and communitarian development. In this sense, it shows itself as a form of deep connection with the vital nucleus of identity, from the self feeling, and also as a possibility of connection and its infinite possibilities of realization, clothing with mythological, ritual, symbolic and emotional meanings, reuniting individuals in a transcendental dimension of reality. This way, the artistic activity could be affirmed in the communitarian and social psychology theoretical and methodological framework, from an epistemological mark, from which one can build a praxis of freedom based in the connection with an affective, emotional, instinctive and intuitive dimension of the identity: in the life experience.